A new species of Aleuroclava Singh (Hemiptera: Aleyrodidae) from Iran - Shahbazvar, Nasrin; Manzari, Shahab; Sahragard, Ahad; Hosseini, Reza; Hajizadeh, Jalil (Zootaxa, 2010)
A new whitefly species, Aleuroclava kharazii Manzari & Shahbazvar sp. nov., is described and illustrated here from several host plant species belonging to Apocynaceae and Rosaceae in Iran. Its taxonomic affinities are briefly discussed.